CONTRIBUTION OF WOMEN FISH MERCHANTS IN ARTISANAL FISHERIES DEVELOPMENT IN OGUN WATERSIDE LOCAL GOVERNMENT AREA, OGUN STATE - OLAOYE, O. J; OJEBIYI, W. G.; OLALEKAN, T. O.; ABDULSALAMI, S. A.; OPELE, I. A. (Nigerian Journal of Fisheries, 2019)
This study investigated the contribution of women fish merchants (WFMs) in artisanal fisheries in Ogun Waterside Local Government Area, Ogun State. A two-stage sampling procedure was used to select 120 fish mammies from four purposively selected fishing communities. Data were collected with the aid of interview guide and analyzed using descriptive and inferential statistics. Results revealed that the mean age and household size of WFMs were 54.01±8.61 years and 12±4 persons respectively. Majority of the WFMs had their goals on profit-making (99.2%), high turnover/quick return from investment (98.3%) and self-employment (89.2%). Major roles played by the WFMs were provision of fishing nets (99.2%), sales of fish catch (98.3%), supply of fishing gears (97.5%), and have control over the fish catch (98.3%). The mean values indicated that high cost of fishing equipment (mean=2.96), and distance of financial institution (mean=2.58) were the most important constraints facing artisanal fisheries. Women Fish merchants’ family type showed a significant association with the roles they played in artisanal fishery enterprises (χ2=9.526, p<0.05). This study concluded that WFMs had contributed to artisanal fisheries through social and economic supports to fisher folks. It is recommended that financial institutions should be established in fishing communities.